A survey of manual vacuum aspiration’s experiences among the new medical graduates in Thailand - Suphanchaimat, Rapeepong (BioMed Central, 2013)
BACKGROUND: Despite Thai laws permitting abortion conducted by registered medical practitioners, unsafe abortion still kills and maims Thai women as a result of inadequate access to safe abortion services. Surgical evacuation of the uterus by manual vacuum aspirator (MVA) is a safe and effective technique recommended by the World Health Organization (WHO) guidelines. This study assessed new medical graduates’ MVA experiences during their clinical years in medical schools. METHODS: Cross-sectional questionnaire surveys on all new medical graduates participating in the annual assembly arranged by the Ministry of Public Health in 2010 and 2012 were applied. Descriptive and inferential statistics were employed for data analysis. RESULTS: The significant minority of new graduates (44% and 43% in 2010 and 2012 batches) had seen but never used MVA. The proportion of graduates who had ‘never seen’ reduced from 32% in 2010 to 23% in 2012 while the proportion of ‘ever used’ had noticeably increased from 24% to 34% in corresponding years. Graduates from medical schools outside Bangkok and vicinity and those reporting confidence in their surgical skills tended to have more MVA experience. The 2012 graduation year was also positively related to higher experience on MVA. CONCLUSION: Though the proportion of graduates who had ever used MVA was still low in 2012, a positive change from that in 2010 was observed. Medical schools outside Bangkok and vicinity provided more opportunities for learning MVA. It is recommended that medical schools, especially in Bangkok and vicinity should provide more MVA learning opportunities for students. Adequate training and regular hands-on MVA practice should be incorporated into a wide range of clinical practice.